2012
DOI: 10.1371/journal.pone.0047793
|View full text |Cite
|
Sign up to set email alerts
|

Regulated Proteolytic Processing of Reelin through Interplay of Tissue Plasminogen Activator (tPA), ADAMTS-4, ADAMTS-5, and Their Modulators

Abstract: The extracellular signaling protein Reelin, indispensable for proper neuronal migration and cortical layering during development, is also expressed in the adult brain where it modulates synaptic functions. It has been shown that proteolytic processing of Reelin decreases its signaling activity and promotes Reelin aggregation in vitro, and that proteolytic processing is affected in various neurological disorders, including Alzheimer's disease (AD). However, neither the pathophysiological significance of dysregu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
85
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(91 citation statements)
references
References 63 publications
2
85
0
Order By: Relevance
“…2B), indicating that Pro-1244 is critically involved in the recognition motif of the unidentified N-t site protease secreted from cortical neurons. Although ADAMTS-4 is one of the candidate protease that catalyzes N-t cleavage (43,44), we found that ADAMTS-4 was able to weakly cleave Reelin-PD (Fig. 2C, lane 8).…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…2B), indicating that Pro-1244 is critically involved in the recognition motif of the unidentified N-t site protease secreted from cortical neurons. Although ADAMTS-4 is one of the candidate protease that catalyzes N-t cleavage (43,44), we found that ADAMTS-4 was able to weakly cleave Reelin-PD (Fig. 2C, lane 8).…”
Section: Discussionmentioning
confidence: 90%
“…We and another group reported recently that ADAMTS-4 can catalyze the N-t cleavage of Reelin (43,44). To determine whether Reelin-PD could be cleaved by ADAMTS-4, Reelin with a FLAG epitope between RR6 and RR7 (ReelinR6-F-R7, 43) and its PD version were used as substrates (Fig.…”
Section: Determination Of the N-t Cleavage Site Of Reelin-mentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, tissue plasminogen activator, shown to be induced by and involved in removal of Aβ aggregates (Tucker et al, 2000), cleaves Reelin at its C-terminal end (Krstic et al, 2012b) and by that modulate its binding to ApoER2 (Nakano et al, 2007). However, the biological significance of the proteolytic processing of Reelin might be more complex (Jossin et al, 2007, Chameau et al, 2009, and likely involves more downstream effects than only reducing binding of Reelin to its receptors, as previously proposed (Kohno et al, 2009).…”
Section: Dysfunctional Reelin Signaling and Its Role In Ad Etiologymentioning
confidence: 87%
“…Proteolysis of proteoglycans by ADAMTS enzymes can have destructive effects, producing matrices with disrupted cell-matrix communication, matrices with impaired fibrillary networks, or matrices with altered biomechanical properties [11]. After numerous comprehensive studies, ADAMTS expression has been found in the CNS [49][50][51][52][53][54][55][56][57][58][59][60] and is known to be changed in disease conditions [44,51,53].…”
Section: The Proposed Functions Of Adamts In Cnsmentioning
confidence: 99%